Students’ mathematical communication through math-talk learning community: Describing levels and components - Yulian, Vara Nina; Wahyudin, Wahyudin; Darhim, Darhim (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
This research aims to analyze and describe the role of the Math-Talk learning community in improving students' mathematical communication. A qualitative approach was adopted in this study, which involved observing the learning process related to patterns, sequences, and number sequences through the Math-Talk learning community method. The written test involved 34 grade VIII junior high school (SMP) students at a public school in Bandung, Indonesia. The results show that the learning components of the Math-Talk learning community, namely: (a) questioning techniques; (b) explanation of mathematical thinking; (c) sources of mathematical ideas; and (d) responsibility for learning, have the potential to improve mathematical communication skills in students. The results of this study show the importance of implementing the Math-Talk method in the school mathematics curriculum to facilitate better and more effective mathematics communication between students and enrich their mathematics learning experience.